2024
DOI: 10.1021/acs.est.3c09280
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl Chloride Microplastics Facilitate Nitrous Oxide Production in Partial Nitritation Systems

Yanying He,
Yingrui Liu,
Xuecheng Li
et al.

Abstract: Partial nitritation (PN) is an important partner with anammox in the sidestream line treating high-strength wastewater and primarily contributes to nitrous oxide (N 2 O) emissions in such a hybrid system, which also suffers from ubiquitous microplastics because of the growing usage and disposal levels of plastics. In this study, the influences of polyvinyl chloride microplastics (PVC-MPs) on N 2 O-contributing pathways were experimentally revealed to fill the knowledge gap on N 2 O emission from the PN system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The sequential reduction of nitrogen oxides (NO x ) is strongly dependent on the electron transport and consumption system (ETCS), and the electron distribution among different reductases directly influences the accumulation of intermediates such as nitrous oxide (N 2 O). As the third most abundant greenhouse gas, N 2 O is approximately 300-fold more potent than CO 2 , enabling it to contribute 50–80% of the entire carbon footprint at wastewater treatment plants (WWTPs) . Meanwhile, denitrification is effectively considered as an important N 2 O sink, mitigating a fraction of N 2 O. , Previous research on microplastics affecting denitrification and associated N 2 O production mainly focused on natural ecosystems, which are fundamentally different from engineered wastewater treatment systems with respect to nutrient concentrations, substrate transfer, and interaction with microplastics. , Our recent studies have demonstrated that long-term exposure to polyethylene terephthalate (PET) and polyvinyl chloride (PVC) microplastics significantly altered N 2 O emissions in wastewater treatment. , However, the mechanisms of the effects of microplastics on N 2 O emission from denitrifying sludge are unknown, especially from the point of view of electron distribution. More importantly, little is known about the effects of BMPs, which are as prevalent in wastewater as conventional NBMPs but exhibit greatly different physicochemical properties and eco-impacts. , …”
Section: Introductionmentioning
confidence: 99%
“…The sequential reduction of nitrogen oxides (NO x ) is strongly dependent on the electron transport and consumption system (ETCS), and the electron distribution among different reductases directly influences the accumulation of intermediates such as nitrous oxide (N 2 O). As the third most abundant greenhouse gas, N 2 O is approximately 300-fold more potent than CO 2 , enabling it to contribute 50–80% of the entire carbon footprint at wastewater treatment plants (WWTPs) . Meanwhile, denitrification is effectively considered as an important N 2 O sink, mitigating a fraction of N 2 O. , Previous research on microplastics affecting denitrification and associated N 2 O production mainly focused on natural ecosystems, which are fundamentally different from engineered wastewater treatment systems with respect to nutrient concentrations, substrate transfer, and interaction with microplastics. , Our recent studies have demonstrated that long-term exposure to polyethylene terephthalate (PET) and polyvinyl chloride (PVC) microplastics significantly altered N 2 O emissions in wastewater treatment. , However, the mechanisms of the effects of microplastics on N 2 O emission from denitrifying sludge are unknown, especially from the point of view of electron distribution. More importantly, little is known about the effects of BMPs, which are as prevalent in wastewater as conventional NBMPs but exhibit greatly different physicochemical properties and eco-impacts. , …”
Section: Introductionmentioning
confidence: 99%